Error Analysis In The News On krjogja.com and The Relationship with Teaching Materials In Indoneian Error Analysis - Dwi Shantika (LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2021)
Language is a communication tool that is systematic which is usually used by humans. Language is also used to communicate between two or more people. Language is divided into two, namely spoken language and written language. Spoken language is a variety of language expressed by spoken media, while written language is a variation of language used with written media. This study aims to describe the forms of written Indonesian errors in the news on the website www.krjogja.com in August 2021 which include: (1) describing the forms of errors in Indonesian in the field of spelling, (2) describing the forms of errors in Indonesian in the fields of (3) describing the relationship Write Indonesian errors in the news on the website www.krjogja.com with the Indonesian Language Error Analysis teaching material. This research belongs to the type of descriptive research. The subject of this research is the website www.krjogja.com and the object of the research is in the form of written Indonesian errors in spelling and syntax. The data collection methods and techniques used were the listening method and the basic tapping technique, followed by the advanced free-involvement-free listening (SBLC) technique, and the note-taking technique. Based on the results of this study, it resulted in the form of written Indonesian errors, namely the connection of written Indonesian errors on the www.krjogja.com site which was used as an alternative teaching material for Indonesian error analysis lectures, one of which was written Indonesian errors in the spelling field as many as 10 forms of errors, and the syntax field. as many as 10 types of errors. Keywords: error analysis, spelling, syntax Abstrak Bahasa merupakan alat komunikasi yang bersifat sistematis yang biasa digunakan oleh manusia. Bahasa juga digunakan untuk berkomunikasi antara dua orang atau lebih. Bahasa dibagi menjadi dua yaitu bahasa lisan dan bahasa tulis. Bahasa lisan adalah ragam bahasa yang diungkapkan dengan media lisan, sedangkan bahasa tulis merupakan varisi bahasa yang digunakan dengan media tulisan. Penelitian ini bertujuan untuk mendeskripsikan bentuk kesalalahan berbahasa Indonesia tulis pada berita di situs www.krjogja.com bulan Agustus 2021 yang meliputi: (1) mendeskripsikan bentuk kesalahan berbahasa Indonesia bidang ejaan, (2) mendeskripsikan bentuk kesalahan berbahasa Indonesia bidang, (3) mendeskripsikanketerkaitan kesalahan berbahasa Indonesia tulis pada berita di situs www.krjogja.com dengan bahan ajar Analisis Kesalahan Berbahasa Indonesia. Penelitian ini termasuk jenis penelitian deskriptif. Adapun subjek penelitian ini adalah situs www.krjogja.com dan objek penelitiannya berupa bentuk kesalahan berbahasa Indonesia tulis bidang ejaan dan sintaksis. Metode dan teknik pengumpulan data yang digunakan ialah metode simak dan teknik dasar sadap, diikuti teknik lanjutan simak bebas libat cakap (SBLC), dan teknik catat. Berdasarkan hasil penelitian ini menghasilkan wujud kesalahan berbahasa Indonesia tulis yaitu kaitan kesalahan berbahasa Indonesia tulis pada situs www.krjogja.com yang dijadikan alternatif bahan ajar perkuliahan analisis kesalahan berbahasa Indonesia salah satunya bentu kesalahan berbahasa Indonesia tulis bidang ejaan sebanyak 10 bentuk kesalahan, dan bidang sintaksis sebanyak 10 bentuk kesalahan. Kata kunci: analisis kesalahan berbahasa, ejaan, sintaksis